Macmillan Dictionary of Historical Terms - Cook, Chris. author. aut Link
X, 350 p.
Keywords: This new edition is fully revised, updated and enlarged. It now contains additional material on non-European history, covering Africa, Latin America and Asia. The dictionary also deals with new terms which have only recently been introduced into the language. This comprehensive work of reference will give both the historian and the layman compact and precise definitions of the key historical terms he is likely to encounter.